PEMBERDAYAAN KELUARGA MISKIN MELALUI PENDEKATAN KELOMPOK - Agus Sjafari (Jurnal Administrasi Publik, 2010)
The Poor Families Empowerment through Group Approach (Case in North Jakarta and Bekasi. This research aims are: (1) Describe and analyze the influence of group characteristics to the level of Empowerment families in North Jakarta and Bekasi, (2) Describe and analyze the influence of empowerment interventions to the level of Empowerment families in North Jakarta and Bekasi in improving family welfare, and (3) Describe and analyze the influence of the level of empowerment Families to the welfare of poor families in North Jakarta and Bekasi.This research has carried out in North Jakarta and Bekasi from April to August 2009. There are two variables used to exemine the effect on the level of empowerment families through PATH ANALYSIS in this research that group characteristics, and empowerment interventions. This research also to axemine the effect of the level of empowerment families to families welfare. Results from this research show that the level of empowerment families is medium level.. Group characteristic and the intervention has significant influence on the level of empowerment families. The level of empowerment families has significant influence on family welfare. Strategy that can be used to improve family empowerment is by implementing group empowerment program.